2013
DOI: 10.4274/tftr.75428
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalji Sendromu Tanısı Alan ve AlmayanTürk Kadınlarda Propriyosepsiyon ve Denge

Abstract: Objective: The aim of this study was to compare proprioceptive acuity and balance parameters in women with and without fibromyalgia syndrome (FMS). Materials and Methods: Thirty women with FMS and 30 healthy controls were enrolled in the study. Functional performance by 6-minute walking test (6MWD), proprioceptive acuity by knee joint position sense using an isokinetic dynamometer, balance by the one-legged balance test and the Berg Balance Scale (BBS) were assessed; and number of falls was recorded in all par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Empirical studies with findings that support this relationship investigated patient groups; for example, a negative association has been found between schizophrenia and somatosensory task performance (i.e., a proprioceptive deficit; Chang & Lenzenweger, 2005;Ritzler & Rosenbaum, 1974;Rosenbaum, Flenning, & Rosen, 1965), although null findings are also known (Leventhal, Schuck, Clemons, & Cox, 1982). A study investigating fibromyalgia reported no difference between patients and healthy controls in the proprioceptive accuracy of the knee (Ulus, Akyol, Tander, Bilgici, & Kuru, 2013), while other findings indicate that people with fibromyalgia rely more on visual feedback in the proprioceptive task of the upper arm (Bardal, Roeleveld, Ihlen, & Mork, 2016). A narrative review on knee osteoarthritis indicated impaired proprioceptive accuracy of the knee of the patients (Knoop et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies with findings that support this relationship investigated patient groups; for example, a negative association has been found between schizophrenia and somatosensory task performance (i.e., a proprioceptive deficit; Chang & Lenzenweger, 2005;Ritzler & Rosenbaum, 1974;Rosenbaum, Flenning, & Rosen, 1965), although null findings are also known (Leventhal, Schuck, Clemons, & Cox, 1982). A study investigating fibromyalgia reported no difference between patients and healthy controls in the proprioceptive accuracy of the knee (Ulus, Akyol, Tander, Bilgici, & Kuru, 2013), while other findings indicate that people with fibromyalgia rely more on visual feedback in the proprioceptive task of the upper arm (Bardal, Roeleveld, Ihlen, & Mork, 2016). A narrative review on knee osteoarthritis indicated impaired proprioceptive accuracy of the knee of the patients (Knoop et al, 2011).…”
Section: Introductionmentioning
confidence: 99%